Leadership for Increasingly Diverse Schools - Theoharis, George; Scanlan, Martin K., 1970- (Educational leadership for equity and diversity, 2015)
Leadership for Increasingly Diverse Schools provides both practicing and aspiring leaders with the theory, research, and practical guidance to lead socially just schools. Today's schools are growing more pluralistic and diverse, and leadership is central to reversing long-standing trends of educational inequities, exclusion, and disparate school outcomes. This book helps readers sharpen their awareness of how multiple dimensions of diversity intersect as well as develop strategies for working with students of all socioeconomic statuses, races, religions, sexual orientations, languages, and special needs. Leadership for Increasingly Diverse Schools provides school leaders the tools to foster teaching and learning environments that promote educational equity and excellence for all students. Special Features: Each chapter focuses on a specific dimension of diversity and discusses intersectionality across other areas of difference, including ability/disability, linguistic diversity, race, socioeconomic status, sexual orientation, gender, religion, and social frontiers. Chapters synthesize literature, provide practical strategies and tools, and include school-level and district-level cases illustrating inclusive leadership. End-of-chapter resources point readers toward further discussion of conceptual elements, practice connections, and research applications. A companion website features modifiable downloads and further resources for each chapter.